Pengalaman Penumpang Terhadap Penerapan Digitalisasi Fasilitas Bandara di Bandara Udara Kualanamu Medan - Dina Yuliana; Kristiono Setyadi; Pribadi Asih (Research and Development Agency of The Ministry of Transportation, 2020)
PT Angkasa Pura II manages Kualanamu Medan Airport. Kualanamu Airport has been develop airport digital facilities. The development of facility technology has aim to improve services for passengers and efficiency of airport operations. This research aims to identify passengers experience in order to improve services through digitizing airport facilities. The research method used descriptive analysis, multiple response analysis and crosstab (cross tabulation). The results has been show that Kualanamu Airport is smart (71.42%). Passengers need technological innovation and realtime facilities to help them in airport. Technological innovation required ie facilities for monitoring baggage and online reservations (74%), applications for shopping / restaurant / entertainmentat airports (73%), customs (70%), vehicle parking (69%) and check in (66%). Realtime Facility required ie facility for check-in (71%), flight schedules and monitoring of baggage movements (64%), airport information facilitiy and boarding gates (63%), vehicle parking at the airport (58%) and customs (54%).